Optimasi Software Effort Estimation Menggunakan Random Forest - Maria Rosario Borroek; Jasmir Jasmir; Fachruddin Fachruddin; Marrylinteri Istoningtyas; Yosefina Venus (Prosiding Seminar Nasional Ilmu Teknik, 2025)
Software development effort estimation is crucial as it is one of the key factors for successful software development. This research employs Random Forest to estimate software development effort. To achieve better results, the study combines the Random Forest method with Genetic Algorithm. The results show that the China dataset provides more accurate estimation compared to the Desharnais dataset, because the China dataset uses relevant feature selection for estimation.